Association of virological breakthrough and clinical outcomes in entecavir-treated HBeAg-positive chronic hepatitis B - Huang, Yi-Jie (PLoS One, 2019)
BACKGROUND & AIMS: To evaluate virological breakthrough (VBT) and the risk of hepatocellular carcinoma (HCC) in HBeAg-positive chronic hepatitis B (CHB) patients receiving entecavir (ETV) treatment. METHODS: A retrospective cohort study was conducted in a tertiary referral hospital and a total of 228 HBeAg-positive CHB patients treated with ETV for more than 48 weeks were enrolled. Clinical outcome measures included HBeAg seroclearance, maintained virological response and the development of HCC. RESULTS: During a median follow-up period of 197 weeks, VBT developed in 26 (11.4%) patients (VBT group), and the other 202 patients without VBT (non-VBT group). The overall cumulative rate of HBeAg seroclearance in the VBT group and non-VBT group were 23.1% and 23.8%, 27.1% and 37.9%, 27.1% and 55.1%, 27.1% and 74.1%, 27.1% and 76.7% from week 48 to 240, respectively(p = 0.013). The cumulative probability of maintained virological responses from week 48 to 240 were 7.69% and 21.78%, 7.69% in the VBT groups and 36.85%, 7.69% and 51.68%, 7.69% and 64.97%, 7.69% and 72.1% in the non-VBT groups, respectively (p<0.001). In the multivariate analysis, age (p<0.001) and virological response at week 24 (p = 0.005) were independently associated with VBT. Cox regression analysis showed that cirrhosis had carried the highest risk for HCC (HR = 4.99, CI = 1.14–21.81, p = 0.033). Subgroup survival analysis by Kaplan–Meier method showed that patients with VBT had higher incidence of developing HCC than without VBT in cirrhotic patients (50% (95%CI = 1–99%) vs 9% (95% CI = 1–9%); p = 0.048). CONCLUSIONS: VBT was associated with adverse clinical outcomes, including a low probability of HBeAg seroclearance, failure to achieve maintained virological responses, and a risk of developing HCC. Patients, particularly with cirrhosis, who had experienced VBT during ETV treatment, more likely developed HCC.